2018
DOI: 10.1177/1474904118780420
|View full text |Cite
|
Sign up to set email alerts
|

Rurality and education relations: Metro-centricity and local values in rural communities and rural schools

Abstract: Rurality and education relations:Metro-centricity and local values inrural communities and rural schools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
1
36
0
6
Order By: Relevance
“…Moreover, the neoliberal promotion of boundlessness, free markets and individualism incorporates an 'unacknowledged metrocentricity', as it provides substantially more opportunities for people in cities than peers in rural areas (Farrugia 2014;Gulczyńska 2019). Beach et al (2019) found that staff in schools in small communities seem to be more proactive in terms of counterdiscourses and more often acknowledge the local than those in small de/industrialised communities. This reportedly affects young people's 'horizons of action' (Hodkinson and Sparkes 1997), a concept largely based on Bourdieu's ideas of habitus and capital, describing people's perceived possibilities.…”
Section: Literature and Key Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the neoliberal promotion of boundlessness, free markets and individualism incorporates an 'unacknowledged metrocentricity', as it provides substantially more opportunities for people in cities than peers in rural areas (Farrugia 2014;Gulczyńska 2019). Beach et al (2019) found that staff in schools in small communities seem to be more proactive in terms of counterdiscourses and more often acknowledge the local than those in small de/industrialised communities. This reportedly affects young people's 'horizons of action' (Hodkinson and Sparkes 1997), a concept largely based on Bourdieu's ideas of habitus and capital, describing people's perceived possibilities.…”
Section: Literature and Key Conceptsmentioning
confidence: 99%
“…In some cases, this may simply be because there are no realistic alternatives geographically, so there is no need to mention place during counselling. However, in some cases, it could be symptomatic of a kind of fatalism in relation to place, and capitulation to 'metrocentrism' and the power geometry (Beach et al 2019;Campbell and Yates 2011;Gulczyńska 2019). This refers to aggregation of all forms of capital around large cities and their centres, accompanied by increasing 'poverty of access' (Gray, Shaw, and Farrington 2006) in rural areas to services, including opportunities for upper secondary and higher education.…”
Section: Focus On the Individual As Unbounded By Placementioning
confidence: 99%
See 1 more Smart Citation
“…The data considered here consist of 85 field days of classroom observations, supplemented with collected teaching materials and interviews with 81 students and 10 teachers. Four researchers adopted a 'collective ethnography' approach (Beach et al 2018;Gordon et al 2006), in which each researcher followed two VET classes. In total, two Vehicle and Transport (VT), two Restaurant Management (RM) and two Health and Social care (HC) programme classes were followed.…”
Section: Methods Methodology and Empiricsmentioning
confidence: 99%
“…Moreover, practically no educational research have been conducted in rural areas (cf. Beach et al 2019). Drawing on interviews with students in the last year of lower secondary school, the aim of the current study is to investigate experiences of violence and harassment directed at sexual minority students in the everyday life of a rural school.…”
mentioning
confidence: 99%